201k views
2 votes
Lol please help me:((((
Given h(x)=−2x−6, find h(3).

Lol please help me:(((( Given h(x)=−2x−6, find h(3).-example-1
User OnkarK
by
4.9k points

2 Answers

4 votes

Hi there!

»»————- ★ ————-««

I believe your answer is:


h(3) = -12

»»————- ★ ————-««

Here’s why:

⸻⸻⸻⸻


h(x) = -2x - 6\\\\------------\\\rightarrow h(3) = -2(3) - 6\\\\\rightarrow h(3) = -6 - 6\\\\\rightarrow \boxed{h(3) = -12}

⸻⸻⸻⸻

»»————- ★ ————-««

Hope this helps you. I apologize if it’s incorrect.

User Anthony Nolan
by
5.4k points
6 votes

Answer:

-12

Explanation:

h(x)=−2x−6

Let x = 3

h(3)=−2*3−6

= -6-6

= -12

User Abdul Yasin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.